Transformational Leadership and Accountability Performance of the Employees in the Public Sector (International Journal of Applied Research in Management and Economics, 2025)
Context & Research Problem: This study explores the impact of transformational leadership on teachers' accountability performance in a public college in Bangladesh. The research addresses the problem of how principals’ leadership styles, characterized by motivation, inspiration, and a shared vision, affect teachers' responsibilities and accountability, both positively and negatively. Methodology & Instrument: A qualitative case study approach was used, involving interviews with eight teachers with varying levels of experience to gather insights into their perceptions of transformational leadership. Thematic analysis was conducted on the interview data to identify key patterns and trends. Results: Findings reveal that transformational leadership positively influences the accountability of motivated, engaged teachers. These teachers reported feeling more responsible, proactive, and committed to their duties under principals who practiced transformational leadership. However, the study also identified a drawback: less motivated teachers sometimes took advantage of the autonomy and trust associated with this leadership style, neglecting some responsibilities. Significance: The significance of this study will lie in its contribution to understanding the complexities of applying transformational leadership in public educational institutions in Bangladesh. It will highlight both the potential positive outcomes, and the challenges associated with transformational leadership. The findings are expected to suggest that while transformational leadership will enhance accountability among dedicated teachers, additional oversight mechanisms may be needed to address performance gaps among less motivated staff.